Higher education in light of Industry 5.0: SERVQUAL-SEM quality dimensions - Rakić, Ana; Glogovac, Maja; Ruso, Jelena; Arsić, Sanela; Milošević, Isidora (Serbian Journal of Management, 2026)
The Industrial Revolution wheels the development of society, and its transformation reflects the upcoming Industrial Revolution. This led to Industry 5.0 and Society 5.0. in many areas, even in education. Therefore, universities should achieve a high level of service quality to align with new industrial trends where humans are expected to be innovative and collaborative in a shared working environment with new digital technologies. Thus, this paper aims to research the relationship among SERVQUAL quality variables of online higher education (Tangibility, Reliability, Readiness, Assurance and Empathy) and their impact on student perception of Industry 5.0 effects on higher education quality. To achieve this aim, the survey was carried out among 532 university students. Structural Equation Modeling (SEM) shows that all analysed relationships among SERVQUAL variables are confirmed and indicate a positive impact. Furthermore, the influence of the mentioned quality variables on the students’ perception of Industry 5.0 effects on higher education quality is also considered. Considering those relationships, Reliability is the only significant variable impacting students’ perception of Industry 5.0 effects on higher education quality. These conclusions could be used to develop a framework for quality improvement of online higher education in Industry 5.0, leading to the base for developing new Society 5.0
Keywords: Industry 5.0; Society 5.0; higher education; SERVQUAL-SEM quality model